Near-infrared luminescence of Nd3+ and Yb3+ complexes using a polyfluorinated pyrene-based β-diketonate ligand. Issue 73 (21st July 2016) - George, T. M.; Varughese, S.; Reddy, M. L. P.
Abstract : Highly efficient near-infrared emitting Nd 3+ and Yb 3+ complexes have been developed based on a new polyfluorinated pyrene-appended β-diketonate ligand. Abstract : A new polyfluorinated β-diketonate ligand containing a pyrene chromophore, namely, 4, 4, 5, 5, 6, 6, 6-heptafluoro-3-hydroxy-1-(pyren-1-yl)hex-2-en-1-one (Hhfpyr) has been designed and employed for the development of a series of near-infrared (NIR) emitting lanthanide complexes (Nd 3+ and Yb 3+ ) in the absence and presence of an ancillary ligand, 4, 7-diphenyl-1, 10-phenanthroline (bath). The isolated NIR-emitting lanthanide complexes [Nd(hfpyr)3 (H2 O)1, Nd(hfpyr)3 (bath)2, Yb(hfpyr)3 (H2 O)3 and Yb(hfpyr)3 (bath)4 ] have been characterized by various spectroscopic techniques and evaluated their photoluminescence properties. The photophysical properties disclosed that the developed pyrene-based β-diketonate ligand is well suited for the sensitization of Nd 3+ as well as Yb 3+ emissions, thanks to the favourable position of the triplet state (T 1 ) of the ligand (Δ E = T 1 – 4 F3/2 = 4700 cm −1 for Nd 3+ and Δ E = T 1 – 2 F5/2 = 6200 cm −1 for Nd 3+ ), as evidenced from the phosphorescence spectra of the corresponding Gd 3+ complexes. Most importantly, the displacement of solvent molecules from the coordination sphere of the NIR emitting lanthanide binary complexes (1 and3 ) with an ancillary ligand markedly enhances the quantum yields ( Φ overall = 0.45 for1 to 1.07% for2 and from 1.69 for3 to 3.08% for4 ) and excited state lifetime values ( τ = 2.80 for1 to 6.16 μs for2 and from 6.88 for3 to 13.45 μs for4 ). Notably, Yb 3+ ternary compound4 with promising NIR luminescence properties was embedded into PMMA matrices, giving rise to a series of PMMA-supported hybrid materials (PMMA@4 ), where the thermal stability and the film-forming properties were significantly enhanced.